Odpowiedzi

2009-12-05T19:52:09+01:00
A) (x+y+1)(2x-y)+(-1)(x-1)(2x+3y)
x*2x+y*2x+1*2x+x*(-y)+y*(-y)+1*(-y)+(-1)*(x*2x+x*3y-1*2x-1*3y)
2x²+2xy+2x-xy-y²-y+(-1)(2x²+3xy-2x-3y)
2x²+2xy+2x-xy-y²-y-2x²-3xy+2x+3y=-y²+4x+2y-2xy

b)-(x+5)(2x+y-3)+(4x-2y)(x-y+3)=
-(x*2x+x*y+x*(-3)+5*2x+5*y+5*(-3)+4x*x+4x*(-y)+4x*3-2y*x-2y*(-y)-2y*3=
-(2x²+xy-3x+10x+5y-15)+4x²-4xy+12x-2xy+2y²-6y=
-2x²-xy+3x-10x-5y+15+4x²-4xy+12x-2xy+2y²-6y=
2x²+5x+2y²-11y+xy+15

c)(3x+y)(x-5y)-x(x+4y-1)-2x(x-9y)=
3x*x+3x*(-5y)+y*x+y*(-5y)-x*x-x*4y-x*(-1)-2x*x-2x*(-9y)=
3x²-15xy+xy-5y²-x²-4xy+x-2x²+18xy=x-5y²

2009-12-05T19:56:35+01:00
A)(x+y+1)(2x-y)+(-1)(x-1)(2x+3y)=2xkwadrat-xy+2xy-ykwadrat+2x-y-1+2xkwadrat+3xy-2x-3y=4xkwadrat+4xy-ykwadrat-4y-1

b)-(x+5)(2x+y-3)+(4x-2y)(x-y+3)=-2xkwadrat-xy+3x-10x-5y+15+4xkwadrat-4xy+12x-2xy+2ykwadrat-6y=-7xy+2xkwadrat+5x+2ykwadrat-11y+15

c)(3x+y)(x-5y)-x(x+4y-1)-2x(x-9y)=3xkwadrat-15xy+xy-5ykwadrat-xkwadrat-4xy+x-2xkwadrat+18xy=-5ykwadrat+x

nie wiem czy dobrze ale sie starałem:(;/
2009-12-05T20:03:01+01:00
A) (x+y+1)(2x-y)+(-1)(x-1)(2x+3y)=
b)-(x+5)(2x+y-3)+(4x-2y)(x-y+3)=
c)(3x+y)(x-5y)-x(x+4y-1)-2x(x-9y)=

a) (x+y+1)(2x-y)+(-1)(x-1)(2x+3y)=2x²-xy+2xy-y²+2x-y-2x²-3xy+2x+3y
=-2xy-y²+4x-4y

b)-(x+5)(2x+y-3)+(4x-2y)(x-y+3)=-2x²-xy+3x-10x-5y+15+4x²-4xy+12x-2xy+2y²-6y=2x²-7xy+5x-11y+15+2y²

c)(3x+y)(x-5y)-x(x+4y-1)-2x(x-9y)=3x²-15xy+xy-5y²-x²-4xy+x-2x²+18xy=x-5y²